Influence of Literacy and Access to Information Media Regarding The Interest of Communities with Land Wakaf at The East Adonara District Office of Religious Affairs (KUA) - Sri Syamsiar, Indriyani; Lutfi, Mukhtar; Wardy Putra, Trisno (Badan Wakaf Indonesia, 2024)
Even though land waqf is included in Islamic teachings, there are still many people who are not aware of the importance of the existence of land for the benefit of the people. Waqf land is regulated in several Indonesian Constitutions which are run by KUA throughout Indonesia. The KUA of Adonara Timur Subdistrict as a forum for channeling land waqf has many shortcomings. Communities, religious leaders, KUA staff, officials who have credibility and power in the social order of life need to be massive in conducting socialization so that literacy, access to information media can support community interest in waqf land. The aim of the study was to determine the effect of literacy and access to information media on the interest in waqf for the people of East Adonara District, East Flores Regency, East Nusa Tenggra Province (NTT). This research was conducted at the KUA Office in East Adonara District with a sample size of 50 respondents who were determined through purpove sampling. This type of quantitative research with data collection methods uses a questionnaire consisting of three variables, namely literacy, access to information media and interest in waqf. Data analysis utilized the Multiple Linear Regression Test which was processed using SPSS version 25. The results showed that the level of influence of literacy on interest in waqf was included in the significant category with a sig. on variable X1 (literacy) of 0.00 ttable of 2.013, the level of influence of access to information media on interest in waqf is a significant category with a sig value. 0.00 ttable 2, 013 and the level of influence of literacy and access to information media on interest in waqf is a significant category with a sig. 0,000 Ftable 3,195. This effect is described in the coefficient of determination test (R2), namely the influence of variables X1 (literacy) and X2 (access to information media) on variable Y (interest in waqf) with a percentage of influence of 86.5%.